Firefly. The complete series [videorecording (DVD)] - Minear, Tim; Minear, Tim; Minear, Tim; Edlund, Ben; Edlund, Ben; Davies, Gareth (Television producer); Espenson, Jane; Gillum, Vern; Greenberg, Drew Z.; Grossman, Michael (Michael N.); Curtis-Hall, Vondie; Grabiak, Marita; et al. (Twentieth Century Fox Home Entertainment, 2003)
The future is nothing like you've imagined. Neither are its heroes.